Local market structure and consumer prices: Evidence from a retail merger - Dennis Rickert; Jan Philip Schain; Joel Stiebale (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2018)
This paper analyzes the effects of a merger between a German supermarket chain and a soft discounter on consumer prices. We exploit geographic variation in prices within retail chains and brands and use a difference-in-differences estimator to compare regional markets with a change in market structure to a control group in unaffected markets. Our results indicate that both insiders and outsiders raised average prices after the merger, particularly in regions with high expected change in retail concentration. In contrast, we estimate price declines in regions that did not experience a rise in concentration but were potentially affected by cost savings within the merged entity. We also provide evidence that remedies imposed by competition authorities were not sufficient to o set anti-competitive effects.
Keywords: D22; L11; L81; L66; K21; 330; Mergers and Acquisitions; Ex-post Merger Evaluation; Retail Markets; RetailPrices; Competition